THIN-LAYER DRYING CHARACTERISTICS AND MODELING OF CELERY LEAVES UNDERGOING MICROWAVE TREATMENT - Demirhan, Elcin; Ozbek, Belma (TAYLOR & FRANCIS INC, 2011)
The effect of microwave drying on moisture content, moisture ratio, drying rate, drying time, and effective moisture diffusivity of celery leaves (Apium graveolens) was investigated. By increasing the microwave output power from 180 to 900W the drying time decreased from 34 to 8min; by increasing the sample amount from 25 to 100g, the drying time increased from 25 to 49min. To determine the kinetic parameters, the drying data were fitted to various models based on the ratios of the differences between the initial and final moisture contents and equilibrium moisture content versus drying time. Among the models proposed, the semi-empirical Midilli et al. model gave a better fit for all drying conditions applied. The activation energy was calculated using an exponential expression based on the Arrhenius equation. The relationship between the drying rate constant and effective moisture diffusivity was also estimated and gave a linear relationship.
Keywords: Activation energy; Celery leaves; Drying kinetics; Effective moisture diffusivity; Microwave drying; HOT AIR; DEHYDRATION; CARROT; PREDICTION; KINETICS; QUALITY; OKRA; Engineering